Driven-dissipative spin chain model based on exciton-polariton condensates - Liew, Timothy Chi Hin (2018)
An infinite chain of driven-dissipative condensate spins with uniform nearest-neighbor coherent coupling is solved analytically and investigated numerically. Above a critical occupation threshold the condensates undergo spontaneous spin bifurcation (becoming magnetized) forming a binary chain of spin-up or spin-down states. Minimization of the bifurcation threshold determines the magnetic order as a function of the coupling strength. This allows control of multiple magnetic orders via adiabatic (slow ramping of) pumping. In addition to ferromagnetic and antiferromagnetic ordered states we show the formation of a paired-spin ordered state|⋯↑↑↓↓⋯⟩ as a consequence of the phase degree of freedom between condensates.